Web-based self-mental health screening and emotional mental problem management in incarcerated juvenile - Nugroho, Prasetyo Aji; Rungreangkulkij, Somporn (MEDISAINS, 2023)
Background: In Indonesia, The Strength and Difficulties Questionnaire (SDQ) is a standard for emotional mental problems screening in incarcerated. However, according to the Ministry of Law and Human Rights regarding the Standards of Health and Care Services Based on Information Technology, there is no information about mental health self-screening computerize-based. During incarceration, incarcerated adolescents have more significant emotional mental problems than adolescents in the community. Therefore, the focus of developing mental health screening applications is juvenile incarceration, but not limited to adolescents in the community.Purpose: The study aims to develop an application for the early detection of emotional mental problems in juvenile offenders that can be monitored by staff, and the juveniles can manage their mental health status during incarceration.Method: This study conducted the ADDIE model, namely, Analysis, Design, Development, Implementation, and Evaluation.Results: An application called MyBehave, a web application-based using the computer, has been created, which has a feature of detecting emotional mental problems and management of emotional mental problems through mental health promotion while in incarceration. Users can carry out early detection independently, and the staff can monitor the development activities to improve mental health. The results of trials conducted on juvenile incarcerated found that this application system was more effective than the manual.Conclusion: This application is helpful for health workers in incarceration in conducting early detection of emotional mental problems and promoting mental health for juvenile incarcerated. This application was cost-effective (paperless), easy to access, can store vast amounts of database information, repeat over time, and does not need clinical training.